PRAKTEK HIDUP KEAGAMAAN BLAIZE PASCAL: ANTARA ATEISME DAN TEISME (Refleksi Kritis Partial Terhadap Praktek Hidup Keagamaan Manusia Modern) - Hipolitus Kewuel (Bahasa Indonesia, 2018)
The aim of this article is to describe the Pascal’s religious life in practice. As a Christians, his life describe the Christians general style of life otomaticaly. Therefore, critical opinions toward Pascal’s religious life in practice means critical opinions toward christian’s religious life in general. In the modern world, this reflection is important to give new paradigm for man and woman how to make ideal religious life comes true. Some problems of theism like Deism, Theodicea, Sceptisism and the concept of religion as an individual and interioristic problem have some implications for the theistic and atheistic simultanously.